Changes in vulnerability among older patients with cardiovascular disease in the first 90 days after hospital discharge: A secondary analysis of a cohort study. Issue 1 (29th January 2019) - Wang, Jinjiao; Dietrich, Mary S; Bell, Susan P; Maxwell, Cathy A; Simmons, Sandra F; Kripalani, Sunil
Abstract : Objectives: (1) To compare changes in vulnerability after hospital discharge among older patients with cardiovascular disease who were discharged home with self-care versus a home healthcare (HHC) referral and (2) to examine factors associated with changes in vulnerability in this period. Design: Secondary analysis of longitudinal data from a cohort study. Participants and setting: 834 older (≥65 years) patients hospitalised for acute coronary syndromes and/or acute decompensated heart failure who were discharged home with self-care (n=713) or an HHC referral (n=121). Outcome: Vulnerability was measured using Vulnerable Elders Survey 13 (VES-13) at baseline (prior to hospital admission) and 30 days and/or 90 days after hospital discharge. Effects of HHC referral on postdischarge change in vulnerability were examined using three linear regression approaches, with potential confounding on HHC referral adjusted by propensity score matching. Results: Overall, 44.4% of the participants were vulnerable at prehospitalisation baseline and 34.4% were vulnerable at 90 days after hospital discharge. Compared with self-care patients, HHC-referred patients were more vulnerable at baseline (66.9% vs 40.3%), had more increase (worsening) in VES-13 score change (B=−1.34(–2.07, –0.61), p<0.001) in the initial 30 days and more decrease (improvement) in VES-13 score change (B=0.83(0.20, 1.45), p=0.01) from 30 to 90 days after hospital discharge. Baseline vulnerability and the HHC referral attributed to 14%–16% of the variance in vulnerability change during the 90 postdischarge days, and 6% was attributed by patient age, race (African-American), depressive symptoms, and outpatient visits and hospitalisations in the past year. Conclusion: After adjusting for preceding vulnerability and covariates, older hospitalised patients with cardiovascular disease referred to HHC had delayed recovery in vulnerability in first initial 30 days after hospital discharge and greater improvement in vulnerability from 30 to 90 days after hospital discharge. HHC seemed to facilitate improvement in vulnerability among older patients with cardiovascular disease from 30 to 90 days after hospital discharge.